Laser induced breakdown spectrocscopy for elemental analysis in aqueous media - Peel, Christopher S. (Cranfield University, 2012)
This thesis is based on extensive experimental work over a three year Ph.D. studentship program sponsored by the AWE on laser induced breakdown spectroscopy (LIBS) for elemental analysis in the water environment. An exhaustive up-to-date literature review has revealed widely different results on the dependence of some of the LIBS parameters on both laser and target parameters. In this research, parametric measurements of the laser-water interaction events were undertaken to validate some quoted values and to attempt to resolve discrepancies within the published results. Analysis of dielectric breakdown in water bulk by focussed laser beam has shown that the threshold laser pulse energy for this was approximately 60% lower in tap water than in distilled water due to impurity content of the former. However, the effect of analyte concentration was found to be much less drastic, giving only a 10% reduction for 2 orders of magnitude of concentration increase of dissolved sodium. Parameters of cavitation bubbles, resulting from the laser induced breakdown process in the water bulk, were measured using two different techniques i.e. probe beam deflection (PBD) and high speed imaging (HSI). Values of bubble diameter before collapse (maximum) and the frequency of the oscillation were found to be different, by 27% for the diameter and by 22% for the frequency, in the results obtained using the two different techniques. The values of the parameters obtained in this study and those found in the literature vary widely and do not show any trend on their dependence with laser pulse energy. It is concluded that large uncertainty in the estimation or control of sampled volume defined by the waist of the laser beam focus render large errors on such measurements. The present work includes parametric measurement of signal-to-noise ratio (S/N) for the detection of signals from analytes dissolved in water for different variable experimental parameters. Optimum values for achieving maximum S/N were obtained. In addition to the spectral and temporal filtering for improving S/N, mechanical filtering techniques were also investigated. This has resulted in the improvement of S/N by more than 25%. The thesis concludes with remarks, based on the analysis of the experimental data, on work for further improvement of sensitivity of the LIBS technique and its wider application as a portable device for in situ, real time point monitoring of elemental contaminants in water.